Multigene phylogeny of the Indo–West Pacific genus Enosteoides (Crustacea, Decapoda, Porcellanidae) with description of a new species from Australia - Alexandra Hiller; Bernd Werding (Zoosystematics and Evolution, 2022)
The porcellanid genus Enosteoides Johnson, 1970, currently containing six species, was raised in the 1970s to contain aberrant Indo–West Pacific forms of the diverse and cosmopolitan genus Porcellana Lamarck, 1801. Here, we describe the most aberrant form as Enosteoides spinosus sp. nov., from the northeast and northwest coasts of Australia and present results on phylogenetic reconstructions of the genus, based on an 1,870 bp alignment of concatenated DNA sequences of three mitochondrial and one nuclear gene. The new species is peculiarly spiny and has a higher morphological affinity to the type species of the genus, E. ornatus (Stimpson, 1858), than to the other congeneric species. Our molecular results indicate that Enosteoides is not monophyletic. The new species and E. ornatus are encompassed in a clade, which does not share immediate common ancestry with the clade containing the other species of Enosteoides. This clade is more closely related to species of Porcellana and Pisidia. Relatively large interspecific genetic distances between and within the two clades, as compared to distances estimated in American pairs of species on each side of the Panama Isthmus, suggest ancient divergence, probably followed by extinction events or low speciation rate. Relatively large intraspecific distances between Australian populations of the new species of Enosteoides from geographically distant locations suggest some level of phylogeographic structure.